Decision structure for transport logistic problem - García-Cáceres, Rafael Guillermo; Trujillo-Díaz, Johanna; Mendoza, Diego (Universidad Pedagógica y Tecnológica de Colombia, 2018)
Planning and decision making in the Transport Logistics Function, TLF, is of high importance in the management of the supply chain. This article aims to develop the problematic and decision structures of the Transport Logistics Function (TLF). The novelties in the characterization of the Transport Logistics Function and its implicit decision processes reported here, complement models proposed by the literature with regard to the determination of elements of the problems and the interrelation of the decisions of the Transport Logistics Function, which have been presented as research perspectives in a supply chain context.